A biosorption of some trace elements from wastewater using fish scales (Barbus luteus) - Maktoof , Afrah A. (Iraqi Journal of Aquaculture, 2023)
Wastewater samples were collected from the sewage treatment plant in Azdinawiya region, south of Al-Nasiriyah city. Barbus luteus fish, weighing 1.15 kg, sampled from the Euphrates River in the Suq Al-Shuyoukh district. Zn, Cd, Cu, and Pb were measured by Flam Automatic Absorption. A powder was made of fish scales. The scales were ground after cleaning. The scales were passed by three types of sieves (250µm, 1mm and 2.36 mm). Test the fish scale powder’s capacity to absorb trace elements from sewage water, 50 g of the powder was placed in a burette, and its capacity was tested five times (zero time, 12 hours, 48 hours, 72 hours, and 96 hours). The results showed that highest removal of Cd, Cu, Zn and Pb according to time after (72 hours 91.946 %, 72 hours at 76.19 %,12 hours at 84.360%, and 72 hours at 58.788 % respectively), while the lowest removal of Cd, Cu, Zn and Pb according to time after (48 hours at 81.879 %, 48 hours at 26.19 %, 48 hours at 54.502 % and Zero time at 39.394 % respectively) and there were significant differences between all-time categories at p. value < 0.05%. Fish scales absorb trace elements from wastewater.